Ethical Issues in Anesthesiology and Surgery - Jericho, Barbara G. (Springer International Publishing : Imprint: Springer, 2015)
Each chapter includes an ethical challenge presented as a clinical case scenario that readers may relate to in their daily practice of anesthesiology and surgery. The ethical issues surrounding each chapter's content are examined in an easily understandable manner for the specific target audience to improve the understanding and management of ethical dilemmas in patient care. Informed consent issues for the adult and pediatric patient, perioperative considerations of do-not-resuscitate orders, ethical issues of drug shortages, transplantation ethics, surgical care of patients and futility, conscientious objection, informed consent and disclosure of surgeon experience, and research and publication ethics are included and based on the experience of the Editor and the roster of contributors.